Avaliação de projetos de investimento em cogeração de energia utilizando bagaço de cana-de-açúcar em biorrefinarias a partir do uso da teoria das opções reais - Tatoni, Walter Milan (2012)
The scenario of continuous increase in consumption of oil products combined with the consciousness that there must be a balance regarding the exploration of natural resources and environmental conservation, has been promoting the search for alternative energy sources. This growing interest has been applied to power generation from biomass of sugarcane, which is becoming more and more common in Brazil, but there is still a huge potential to be explored. Within this context it becomes relevant to decision making for investments in cogeneration projects and this paper intended to increase the analysis and decision making using the Real Options Theory, a tool for adding value to the uncertainties, the model fits perfectly Brazilian Energy regulatory framework, where large energy price volatilities are observed over the years. This study aims is to determine the best moment to invest in cogeneration units. The structure of the study was divided into three scenarios for biorefineries size, 2 million of crushing capacity of sugar cane per year, 4 million and 6 million, thus aiming to have a representation of the all biorefineries size in the country. In addition, we analyzed three scenarios of energy price and linked volatility, as the main variable of this type of project viability is the price of energy. Volatilities were calculated according to the historical price in regulated environment, twice the regulated environment and projection of PLD, representing, respectively, low, medium and high, volatile energy price. After this, were elaborated nine decision trees, which show for the investment managers that in a scenario of low volatility creates value to be positioned and have the real option to invest or postpone investment for any size of plant. In the scenario with an average volatility, the manager is advised to be positioned in plants of medium to large for the feasibility of the investment. Finally, when the price scenario is highly volatile, there is a greater risk and there is a greater probability of viability of investment in large plants.